Clinicopathological features and prognostic outcomes of molecularly defined entities in the new edition of the WHO classification of sinonasal carcinoma - Vuong, Huy Gia; Le, Thoa; Le, Trang T.B.; Le, Hieu Trong; El-Rassi, Edward T.; McKinney, Kibwei A.; Dunn, Ian F. (Frontiers in Oncology, 2023)
Introduction We investigated the clinicopathological features and prognoses of the new molecularly defined entities in latest edition of the World Health Organization (WHO) classification of sinonasal carcinoma (SNC) Methods Integrated data were combined into an individual patient data (IPD) meta-analysis. Results We included 61 studies with 278 SNCs including 25 IDH2-mutant, 41 NUT carcinoma, 187 SWI/SNF loss, and 25 triple negative SNCs (without IDH2 mutation, NUTM1 rearrangement, and SWI/SNF inactivation) for analyses. Compared to other molecular groups, NUT carcinoma was associated with a younger age at presentation and an inferior disease-specific survival. Among SNCs with SWI/SNF inactivation, SMARCB1-deficient tumors presented later in life and were associated with a higher rate of radiotherapy administration. SMARCA4-deficiency was mostly found in teratocarcinosarcoma while SMARCB1-deficient tumors were associated with undifferentiated carcinoma and non-keratinizing squamous cell carcinoma. Conclusion Our study facilitates our current understanding of this developing molecular-defined spectrum of tumors and their prognoses.